Enhancing young learners' english vocabulary learning with gamified flashcards: A community service at SD St. Theresia Marsudirini 77 Salatiga - Payungallo, Aubreylia Visca; Alridya, Briana Putri; Ardiyani, Rizky Tri; Setyowati, Sukma Ayu Dwi; Kisnanto, Yustina Priska (Nur Science Institute, 2026)
English learning for young learners requires concrete, interactive, and age-appropriate learning materials. The use of gamified flashcards, combined with audiovisual learning, is an effective method. Twenty-eight second-grade students at St. Theresia Marsudirini 77 Elementary School in Salatiga participated in this community service program. The student group conducted classroom observations, interviewed English teachers, and created modified flashcards for the games Act It Out and Fast Four. Results showed that students were enthusiastic, actively participated, and were able to remember and use vocabulary in simple contexts. Teacher feedback confirmed that the flashcards were easy to understand, well-designed, and appropriate for the students' needs. Despite limitations such as the need for simpler instructions for young children, the program demonstrated that creative teaching tools and gamification can make English learning more enjoyable, meaningful, and effective. The program emphasized the importance of using physical visual aids in early English education to support vocabulary development and build children's confidence in communication.